Menelusuri Dinamika Pengangguran Terbuka: Peran Penduduk, Pertumbuhan Ekonomi, dan Inflasi di Indonesia (2000-2021) - Santa Brigita Lasmaria Hutagalung; Martin Luter Purba; Elvis F Purba (CV. Ulil Albab Corp, 2024)
The aim of this study is to analyze the factors influencing the open unemployment rate in Indonesia from 2000 to 2021, namely population size, economic growth, and inflation. The data used in this study are secondary data spanning from 2000 to 2021, sourced from the Central Statistics Agency (BPS) and Bank Indonesia (BI). Data processing was conducted using multiple linear regression analysis with SPSS 22 software.The research findings indicate that: 1) The population size has a negative and significant effect on the open unemployment rate in Indonesia from 2000 to 2021. 2) Economic growth has a negative but insignificant effect on the open unemployment rate in Indonesia from 2000 to 2021. 3) Inflation has a positive and significant effect on the open unemployment rate in Indonesia from 2000 to 2021. Simultaneous testing (F-test) shows that the population size, economic growth, and inflation collectively influence the open unemployment rate in Indonesia from 2000 to 2021. Furthermore, based on the coefficient of determination (R²) of 0.368, it means that 36.8% of the open unemployment rate in Indonesia can be explained by Population Size, Economic Growth, and Inflation. The remaining 63.2% may be explained by other variables outside the scope of this study model.